PENGARUH PEMBERIAN PUPUK KASCING DAN PEMOTONGAN UMBI TERHADAP PERTUMBUHAN DAM PRODUKSI BAWANG MERAH (Allium ascalonicum L.) - Eniwati Harianja; Syamsul Bahri; Boy Riza Juanda (Bajang Institute, 2024)
This study aims to determine the effect of vermicompost fertilizer and tuber cutting and the interaction of the two treatments on growth and production on the growth and production of shallots (Allium ascalonicum L.)